The Influence of Leadership Style on Employee Performance at The Cicantayan Sub-District Office - Wicaksono, Muhammad Rifqi Satya; Sampurna, Rizki Hegia; Amirulloh, M. Rijal (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
The aim of this study is to examine the impact of leadership style on employee performance in the Cicantayan sub-district office located in Sukabumi Regency. The research will utilize quantitative methods with a descriptive approach. The target population consists of all employees working at the Cicantayan District Office, amounting to 22 individuals who will be included as the sample for this study. Data collection will involve the use of questionnaires and a review of relevant literature. The findings indicate a positive and significant relationship between leadership style and employee performance, confirming the initial hypothesis that increasing leadership style positively influences employee performance